2011
DOI: 10.1111/j.1467-9663.2011.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

LEADER+ TERRITORIAL GOVERNANCE IN POLAND: SUCCESSES AND FAILURES AS A RATIONAL CHOICE EFFECT

Abstract: The paper analyses the processes of implementing territorial governance using the example of local action groups (LAGs) supported by the LEADER+ Pilot Programme (2005–2008) in Poland. It concludes that the partnership successes and dysfunctions observed resulted from the rationality on the part of bureaucrats and local stakeholders, which may be explained in terms of second‐generation rational choice theories. The main role in the partnerships was that played by local authorities, which often sought to retain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
0
17
0
3
Order By: Relevance
“…information exchange in face-to-face interactions) is an important outcome of governance. this is a critical function of territorially embedded networks, which is significantly connected with the concept of neoendogenous development discussed in economic geography and rural studies (ray 2006;Adamski and Gorlach 2007;Furmankiewicz 2012). the SnA analysis showed that dense cooperation ties were linked with enhanced flows of resources required for fulfilling various local development needs.…”
Section: Network Structures In Leader Functional Regionsmentioning
confidence: 93%
See 2 more Smart Citations
“…information exchange in face-to-face interactions) is an important outcome of governance. this is a critical function of territorially embedded networks, which is significantly connected with the concept of neoendogenous development discussed in economic geography and rural studies (ray 2006;Adamski and Gorlach 2007;Furmankiewicz 2012). the SnA analysis showed that dense cooperation ties were linked with enhanced flows of resources required for fulfilling various local development needs.…”
Section: Network Structures In Leader Functional Regionsmentioning
confidence: 93%
“…in eu rural development policy, for example, cross-sectoral partnerships have become the dominant operational model in the form of the leAder programme (liaisons entre actions de développement de l'économie rurale). the principles and aims of the programme are directly salient with notions of territorial or regional governance (Böcher 2008;Furmankiewicz 2012) and neo-endogenous development (ray 2006; Adamski and Gorlach 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Studies conducted in post-socialist states (Furmankiewicz 2012;Furmankiewicz and MackenWalsh 2016;Kovach and Kucerova 2006;Macken-Walsh and Curtin 2012;Majerova 2009;Marquardt et al 2012;Pawłowska 2017;Zajda 2014;Zajda and Kretek-Kamińska 2013) indicate numerous problems associated with intersectoral collaboration between these organisations. In Poland (similar to other countries), local action groups have traditionally been dominated by local power elitesrepresentatives of the public sector (Furmankiewicz and Macken-Walsh 2016, p. 14).…”
Section: Collaboration Between Rural Non-governmental Organisations Amentioning
confidence: 99%
“…Thus, LEADER has not reached all potential actors and interest groups (Shortall, 2008), leaving scope for inclusion of disadvantaged groups or less involved actors, such as rural women, young people or migrants. Also the full potential of the role of farmers and the opportunities for linkages to other economic actors were addressed to a limited degree in most Local Action Groups (LAG) (Oedl-Wieser, 2010;Thuessen, 2010;Furmankiewicz, 2012, Granberg et al, 2015. Furthermore, it has to be acknowledged that the fi nancial support for LEADER as a Community Initiative was very small, compared to the CAP and Structural Funds budgets, implying a limited (quantitative) impact on rural development.…”
Section: The Idea Of the Leader Approachmentioning
confidence: 99%